Evaluasi Ketidakpastian Pengukuran Multi-Unsur Dalam Mineral Zirkon Dengan Metode Analisis Aktivasi Neutron - Sukirno, Sukirno; Murniasih, Sri; Rosidi, Rosidi; Samin, Samin (BRIN Publishing, 2015)
The evaluation of multi-elements analysis has been carried out with calculation of element uncertainy in the zircon mineral from Sampit (Central Kalimantan) dan Bangka has been evaluated by the Neutron Activation Analysis (NAA) method. The purpose of this research is determination of composition and value of multi-elements uncertainty in the mineral of zircon to fulfil the requirements of ISO/IEC guide 17025-2008 that applied at NAA laboratory. The result of analysis using gamma spectrometry with a HPGe detector showed of 21 detected elements, divided into three groups (major, minor, and trace). Evaluation of uncertainty estimation should be done to increase quality and confidence rate of analysis results. The result of testing are not mean without calculation of uncertainty. Therefore, it was assessed the uncertainty measurement of all elements analysis in zircon mineral. The results of quantitative analysis is Zr with the highest concentration value of 38.986% and value of uncertainty is 0.331% so that value of real concentration is 38.986 ± 0.331%. In the form of oxide (ZrO2) has concentration of 52.661±0.45%. Sb element is the lowest element detected with value of concentration and uncertainty is 7±0,3 µg/g. In the form of oxide (Sb2O3) has concentration is 17±0.9 µg/g. The oxide composition and the must important of chemicals in the zircon sand mineral more significant from Sampit which quantitative composition areZrO2+HfO2 (53-55%), F2O3 (5-6%), TiO2 (13-14%), Al2O3 (1.5-2%) and SiO2. Elements ofSi(SiO2) can not be determinedbyNAAmethodbecauseSi cross-sections is verysmall.